Belimumab in the treatment of systemic lupus erythematosus: 20 years of basic research, 10 years of clinical practice - E. L. Nasonov; T. V. Popkova; A. M. Lila (Научно-практическая ревматология)
Currently, strong evidence has been obtained for the fundamental role of pathological activation of B cells in the pathogenesis of immunoinflammatory (autoimmune) rheumatic diseases (IMRD), and drugs that specifically modulate the function or cause depletion of various subpopulations of B cells and plasma cells are considered a promising direction. pharmacotherapy of these diseases. of particular interest is belimumab (BLM), a human monoclonal antibody (mAb) (IgG1λ) to BAFF (B cell-activating factor belonging to the TNF family), which is the first “targeted” biological drug specially developed for the treatment of systemic lupus erythematosus (SLE). The efficacy and safety of BLM in SLE in adults and children, including lupus nephritis, in combination therapy with rituximab, steroid-sparing effect, the ability to prevent irreversible damage to internal organs dictate the need for its wider application in clinical practice.